2001
DOI: 10.1177/089686080102100413
|View full text |Cite
|
Sign up to set email alerts
|

Late Renal Transplant Failure: An Adverse Prognostic Factor at Initiation of Peritoneal Dialysis

Abstract: Background Early renal transplant failure necessitating a return to dialysis has been shown to be a poor prognostic factor for survival. Little is known about the outcome of patients with late transplant failure returning to dialysis. It was our clinical impression that late transplant failure (>2 months) carries an increased morbidity and mortality risk in patients returning to dialysis. Objective To determine whether patients with a failed renal transplant have an outcome different to those on dialysis wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 23 publications
(23 reference statements)
1
31
2
Order By: Relevance
“…Nevertheless, the majority of patients with a failed allograft initiate hemodialysis (HD) as their next renal replacement modality. 2 The reasons very few patients initiate PD after failed allograft may be related to the perceived uncertainty about the success of PD in this patient population because of the paucity of outcome studies [5][6][7] and concerns about an increased risk of therapy-related infections. 6,8 The increased risk of infection is assumed to be sustained after allograft failure because of continuation of immunosuppressive therapy to preserve residual allograft function.…”
Section: Abstract: Transplant Failure; Peritoneal Dialysismentioning
confidence: 99%
“…Nevertheless, the majority of patients with a failed allograft initiate hemodialysis (HD) as their next renal replacement modality. 2 The reasons very few patients initiate PD after failed allograft may be related to the perceived uncertainty about the success of PD in this patient population because of the paucity of outcome studies [5][6][7] and concerns about an increased risk of therapy-related infections. 6,8 The increased risk of infection is assumed to be sustained after allograft failure because of continuation of immunosuppressive therapy to preserve residual allograft function.…”
Section: Abstract: Transplant Failure; Peritoneal Dialysismentioning
confidence: 99%
“…This negative bias was reinforced by case reports of PD patients developing ‘unusual’ infections when concomitantly treated with immunosuppressive drugs . Moreover, the studies by Andrews et al and Sasal both suggested a trend towards higher peritonitis rates in the PD patients receiving immunosuppression. However, these studies were in an era when Y‐disconnect PD systems were being introduced (between 1989 and 1996) and peritonitis rates were considerably higher (up to 1 in 9.7 patients months) than current infection rates.…”
Section: Introductionmentioning
confidence: 99%
“…The initial studies of patients returning to PD after graft loss were small, single‐center studies with data collection spanning several years (10,11,14,18,19). Most of these observed equivalent or better survival for PD patients returning to DAGL when compared with transplant‐naïve PD patients; they have been since confirmed by two large studies (15,16).…”
Section: Modality‐specific Survival For Patients Returning To Daglmentioning
confidence: 99%
“…Sasal et al. studied 42 patients with failed renal allografts returning to PD between 1989 and 1996 compared to an incident historical cohort of 43 transplant‐naïve PD patients (18). Matched only by age and diabetes, the failed‐transplant group had worse outcomes with more technique failure and decreased survival.…”
Section: Modality‐specific Survival For Patients Returning To Daglmentioning
confidence: 99%
See 1 more Smart Citation